Imaging in trauma - Hassan, Radhiana (2018)
The lecture topic is imaging in trauma, thus there will be a brief discussion on different imaging modalities that can be used in trauma cases. The focused will be on CT scan which is the imaging modality of choice in these cases. Case scenarios commonly encountered in daily clinical practice will be given and discussed to illustrate the importance of this topic.